A governança ambiental como possibilidade no auxílio em decisões que envolvem a litigância climática: o caso da Colômbia e a visão adotada na justiça brasileira - Rohde, Carolina de Oliveira (2023)
The intensification of anthropogenic disasters worldwide has led climate change to become the greatest challenge to face today. Given this, numerous regulatory instruments involving the climate emergency have been signed by nations as a way of minimizing its effects, although little progress has been made in mitigating emissions, and this is primarily due to the significant influence of economic and political factors on decisions involving the climate. Hence, this study sought to outline a study of climate litigation decisions through a comparative analysis between the STC 4360-2018 decision of the Colombian Supreme Court in contrast to the existing actions in the national legal system, especially in the Brazilian Federal Supreme Court. With this, we aimed to investigate anthropogenic interference and its relationship with climate change and how environmental governance can be a viable measure to positively influence decisionmaking involving climate litigation. Regarding the proposed problem, we sought to answer the following: “What are the limits and possibilities of environmental governance to assist in decisions involving climate litigation based on the Colombian decision and existing precedents in Brazilian justice?” To this end, the method followed the quadrinomial approach, basic theory, procedure, and technique. Given the transdisciplinary nature of the climate issue, the systemiccomplex method was adopted, making it necessary to go beyond the law and into other areas, including science, politics, economics, and society, to respond to the issue. As for the basic theory, the systemic-complex theory was adopted and based on the lessons of Fritjof Capra and Edgar Morin; authors such as Bruno Latour, Déborah Danowski, and Eduardo Viveiros de Castro were also utilized to cover anthropocentrism. For climate change and its consequences, authors such as Hervé Kempf and Anthony Giddens were used; climate litigation was covered by data from Jacqueline Peel, Hari M. Osofsky, Gabriel Wedy, Joana Setzer, Kamila Cunha, and Amalia Botter Fabbri. Lastly, concerning climate governance, the teachings of Ana Maria de Oliveira Nusdeo, Ernani Contipelli, Jacqueline Peel, Hari M. Osofsky, and Elinor Ostrom were used. The procedure adopted was bibliographical research and a case study, using the techniques of summaries, fiches, and comparative synthesis. Therefore, regarding the results obtained, albeit briefly, it was possible to conclude that strategic climate litigation is generally positive and functions as an integral element of climate governance with the fundamental role of shaping state actors in achieving effective measures to curb greenhouse gas emissions and combat the impacts of climate change, through pressure from non-state actors, such as civil society, through multi-level articulation. Nevertheless, it should be noted that not everything is smooth sailing, and litigation is faced with challenges that must be addressed, including difficulty in accessing justice, the lack of political interest from governments in the climate agenda, skepticism of judging bodies, and the prevalence of economic interests that go against the environmental agenda.